2007
DOI: 10.1080/08941930601126322
|View full text |Cite
|
Sign up to set email alerts
|

Orthotopic Total Aortic Root Replacement Model in Adult Sheep

Abstract: Prosthetic heart valves undergo mandatory preclinical animal testing prior to human clinical trials. Historically, a non-site-specific placement of a valve prosthesis has been commonly performed; however, recently site-specific placement continues to attract interest. Various animal models have been used for preclinical evaluation of both aortic and mitral valve prostheses; however, a universally accepted animal model for orthotopic total aortic root replacement with acceptable early and late mortality for lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…In other similar studies, the internal temperature was lowered even further, to 28 °C6,10 or 25 °C. 18 We found that administering ice-cold cardioplegic solution and routinely applying ice-cold saline directly into the pericardium and left ventricle were cardioprotective. Cooling down the cardioplegic solution to 4 °C or using saline slush has also been described in literature.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In other similar studies, the internal temperature was lowered even further, to 28 °C6,10 or 25 °C. 18 We found that administering ice-cold cardioplegic solution and routinely applying ice-cold saline directly into the pericardium and left ventricle were cardioprotective. Cooling down the cardioplegic solution to 4 °C or using saline slush has also been described in literature.…”
Section: Discussionmentioning
confidence: 97%
“…19 Consequently, high on-table mortality rates, ranging from 9% to 33%, have been reported. 1,18,21,24 Furthermore, the incidence of mortality during the first 30 d after surgery, directly related to the surgical procedure, is often high, ranging from 17% to 50%. 1,2,16,18,21 Therefore, optimizing cardioprotective strategies during surgery would improve postoperative survival.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sheep have long been established as an animal model in heart valve research for the preclinical safety assessment of prosthetic and bioprosthetic cardiac valves [1][2][3]. The cardiovascular system and blood coagulation profile of sheep is similar to humans and the aortic root allows for implantation and evaluation of cardiac devices using standard cardiopulmonary bypass and anesthetic protocols [1].…”
Section: Introductionmentioning
confidence: 99%
“…Stephen Q Garofolo 1 *, Christine Watson 2 , Richard W Bianco 1 and Nicholas A Robinson 1,2 1 Experimental Surgical Services, University of Minnesota Medical School, USA 2 University of Minnesota College of Veterinary Medicine, USA of leaflets, structural valvular dysfuction, paravalvular leaks, or other surgical complications leading to congestive heart failure and death. Early deaths unrelated to the valve or surgical procedure, such as environmental stress or natural disease are not common, and while precautionary steps in the husbandry and management of the animals are taken to prevent them, they do occur occasionally.…”
Section: Introductionmentioning
confidence: 99%